An experimental reseach and analysys of skidder dynamic loads in transmission at the time of machine start - Borys, Mykola (Forestry, Forest, Paper and Woodworking Industry, 2024)
The article gives the results of experimental investigations of wheel skidder loads appearing in transmission’s elements at the time of wheel skidder starting. The reliability, longevity and skidding capability of wheel skidder that basis on wheel industrial tractor depend to a great extent on their hauling, road hold abilities. These abilities are substantially connected with parameters of engine, transmission and body layout machines; and a series of indices is used to evaluate the mentioned parameters [1, 2, 3]. The experimental investigations were carried out for the determination the main indices of tractive abilities, to confirm the adequacy of the developed mathematical model and to get the reference physical values for traction calculation and vibration analysis in transmission mechanism. The investigations were conducted in site conditions on typical tralling drags. Skidder LТ-157 was an object of the investigations. The complect of measuring equipment was developed and made on experimental machine for the tests realization. It’s scheme was on fig.1. The operator seat and register equipment were placed in driver cabin. After analyzing of the experimental results the maximum values of torques at the half shafts of front driving axle and back driving axle were obtained of skidder LТ-157; and also their dependences on the size of bunches at the time of machine start were plotted (fig. 2). Since the part of machine dead (unladed) weight falling on the front axle makes up about 54 %, the adhesion moment of front wheels is larger. So the values of torques at front half shafts at the time of gradual start are somewhat larger. In the case of sudden start the dynamic loads of the transmission increase and are 1,5-2,3 times larger than in the smooth start conditions. The analyses of dynamic load indices of LТ-157 machine (fig. 2) shows that at the time of its start with a timber bunch the torque values at the half shafts of back axle are 1,1-1,4 times larger than at the half shafts of front axle. The increase of torques at the half shafts of back axle is caused by its additional charge with the part of timber bunch weight. Besides, the timber bunch increments the inertia moments of reciprocating masses that cause the raising the dynamic loads of transmission. Fig. 3 represent the dependences of maximum torque on half shafts wheeling skidder LТ-157 during the start at different gears with a timber bunch. It is obvious that the machine start from rest, which continue 5-7 sec is specific: the torque at semi axles has two maximum (peak) values. The first peak of the torque curve corresponds to the start process of the machine; the second peak shows the beginning of timber bunch motion. Analyzing the existing dependences we can see that the start process at low gear is considerably easier than the start at the 4th gear. It can be explained in such a way: when starting at higher gears the gripping mechanism with a timber bunch at first deviates; and the tractive effort in the hauling cable grows in discrete steps (spasmodically) at the expense of inertial efforts arising from the cargo loosening. The carried out investigations allowed to obtain the experimental data concerning the loadings in transmission elements at different application conditions and showed that the design char-acteristics of skidders and their application conditions call forth the no uniform torque is distribution: back semi axles can be 1,5-2,0 times over laden as compared with front semi axles. The given results of the experimental investigations can be used for improving of the transmission constructions and general body layout of wheel skidders that will assist the growth of their reliability and skidding capability